Efek Antihiperlipidemia Kombinasi Ektrak Kelopak Bunga Rosella dan Ekstrak Daun Bawang Kucai - Dwi Ningsih; Samuel Budi Harsono; Anas Diah Kusumawati; Dinda Nur Mahmudah (Jurnal Farmasi Indonesia, 2017)
Research was conducted to determine the antihyperlipidemic activity of the combination of Roselle Petal AndGarlic Chives Leaves ethanol extracton hyperlipidemic rats. To determine the potential effects of a combination of garlic chives leaves and rosella, the test animals were divided into seven treatment groups consisting of a hyperlipidemic control group, rosella group (500 mg / KgBW), garlic chives leaves group (110 mg / KgBW), the combination of Roselle Petal And Garlic Chives Leaves respectively 125 : 82.5 mg / KgBW, 250 : 55 mg / KgBW, and 375 : 27.5 mg / KgBW.Total cholesterol test results obtained percent reduction in total cholesterol rosella group (500 mg / KgBW) amounted to 11.49%, garlic chives leaves group (110 mg / KgBW) amounted to 13.70%, the combination of roselle petal and garlic chives leaves125 : 82.5 mg / KgBW, 250 : 55 mg / KgBW, and 375 : 27.5 mg / KgBW, respectively by 40.60%; 46.80% and 32.80%. The test results obtained percent decrease in triglyceride levels of triglyceride levels rosella group (500 mg / KgBW) amounted to 16.40%, garlic chives leaves group (110 mg / KgBW) amounted to 27.68%, combination of roselle petal and garlic chives leaves 125 :82.5 mg / KgBW, 250 : 55 mg / KgBW, and 375 : 27.5 mg / KgBW, respectively by 18.67%; 45.24% and 15.76%.The combination of roselle petal and garlic chives leaves250 : 55 mg / KgBW more effective to reduce total cholesterol and triglyceride blood of test animals than others.